Empirical determinants of zombification in petrochemical firms. The case of Colombia - Rahmer, Bruno de Jesus (2025)
Corporations with persistently negative profitability, excessive leverage, and declining real revenue growth, are colloquially referred to as "zombie firms" due to their economically unviable nature.Such financially distressed entities operate in both developed economies and emerging markets. This paper quantifies the financial performance of zombie firms within Colombia’s petrochemical cluster using a five-component methodology. The research applies a probit regression, a comparative analysis of financial constraint indices, an investment-cash flow sensitivity model, a corporate flow of funds analysis, and a cash flow sensitivity of cash model. The probit model establishes that indebtedness, minimal asset tangibility, and inadequate operating cash flow function as the primary statistically determinant predictors of zombie status. The comparative analysis of financial constraint indices confirms the superior discriminatory power of the Whited-Wu index over the Kaplan-Zingales and Size-Age alternatives for classifying these corporations. Furthermore, the investment-cash flow sensitivity model establishes that zombie firms systematically curtail capital expenditures in response to their distressed nature, a behavior not observed in their solvent counterparts. The corporate flow of funds analysis derives a structural explanation: an inability to generate internal cash flow and volatility in working capital primarily cause the financing deficit of underperforming entities, whereas these factors are not determinant for solvent corporations.Finally, the cash flow sensitivity of cash model confirms that a precautionary motive dictates the cash accumulation policies of zombie firms, a behavior absent in financially viable entities.